As vestes brancas: uma representação simbólica de elementos socioculturais: Zé Pelintra, o boto e o malandro da gafieira - SALES, Flavio Gilberto Barbosa (2021)
This work proposes a memorial of a scenic work called "The White Vests" created in 2004 for the Open Scene event, an extension project of the School of Theater and Dance of the Federal University of Pará (UFPA), in Belém, where I represented three elements of Brazilian cultural diversity, experienced in the practice of scenic performance, while personalities, in different phases of my life as an actor and dancer (O Boto - as an element that represents the mythical / legendary universe of the Amazonian man, the entity of Umbanda Seu Zé Pelintra - which represents Afro-Amerindian religiosity and the Gahora Dance-rhinoceros - Brazilian type that represents the social aspect). Proposing an analysis of the context of scenic creation and the relationships of my affective memories and with all the elements that influenced me as a living creature of a culture and as a creative interpreter. Analyzed on conceptual bases (Memory, Semiotics, Anthropology, Performance and Restored Behavior), and on different compression levels.